Towards a Multidisciplinary Approach to Improve Cattle Health and Production in Uganda - Fuente, José de la; Contreras, Marinela; Kasaija, Paul D.; Gortazar, Christian; Ruiz-Fons, Jose F.; Mateo, Rafael; Kabi, Fredrick (Vaccines, 2019)
A meeting and course supported by the Vice-Presidency for International A airs of the Spanish National Research Council (CSIC) and the National Agricultural Research Organization of Uganda (NARO) were held at the National Livestock Resources Research Institute (NaLIRRI) in Nakyesasa, Wakiso, Uganda on September 2–9, 2019. The activities were conducted within the collaboration program between the Institute of Game andWildlife Research (IREC, CSIC-UCLM-JCCM, Spain) and NARO for the development of vaccines and other interventions for the control of cattle ticks in Uganda.
Keywords: Cattle; Tick; Vaccine; Economy